2021
DOI: 10.1097/md.0000000000027402
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the problem-based learning in medical cell biology education

Abstract: Background: Problem-based learning (PBL) was widely adopted in medical cell biology education for Chinese student; however, there was no systematic analysis to prove PBL was much more effective than lecture-based learning (LBL). Our aim is to evaluate the effectiveness of PBL on cell biology curriculum compared with LBL. Method: We systematically searched the publications related to PBL teaching approach in cell biology curriculum for medical education from databases un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Many studies comparing the level of improvement in learning outcomes, scores of the PBL method compared with the traditional method give similar results. Author Xu, after searching and selecting 9 high-quality studies for inclusion in a meta-analysis, noted: The mean score (95% confidence interval) of the total PBL program test score was significantly higher than 0.89 (0.52 -1.26) compared to the traditional class at the end of teaching the cell biology module 0.53 (0.29-0.78) [13]. Gurpinar's study, when comparing the average scores obtained on 25 questions on the knowledge test in the public health class, found that the PBL group scores higher than the traditional group (65.0 versus 60.5).…”
Section: Comparison Of Knowledge Assessment Results Between Two Groupsmentioning
confidence: 99%
“…Many studies comparing the level of improvement in learning outcomes, scores of the PBL method compared with the traditional method give similar results. Author Xu, after searching and selecting 9 high-quality studies for inclusion in a meta-analysis, noted: The mean score (95% confidence interval) of the total PBL program test score was significantly higher than 0.89 (0.52 -1.26) compared to the traditional class at the end of teaching the cell biology module 0.53 (0.29-0.78) [13]. Gurpinar's study, when comparing the average scores obtained on 25 questions on the knowledge test in the public health class, found that the PBL group scores higher than the traditional group (65.0 versus 60.5).…”
Section: Comparison Of Knowledge Assessment Results Between Two Groupsmentioning
confidence: 99%
“…Overall, our findings were in accordance with previous studies, in which the case-based PBL could improve the student' grades and be adapted to different courses. [19][20][21][22][23] With the willingness of good performances in the class, students would strengthen their independent learning and review carefully, which was sometimes beyond the goal designed. [24] Students' feedback of the integrated PBL for the basic and clinical medicine courses were collected.…”
Section: Discussionmentioning
confidence: 99%
“…By December, 2021, Ding et al (2023) found that the PAD class approach has been implemented in more than 1000 schools and more than 3,400 papers and studies on it were published in China. Several others were published by Chinese proponents of the technique in international journals (Li et al, 2021;Xu et al, 2021;Wang et al, 2021).…”
Section: Pad Classmentioning
confidence: 99%